Introducing strut efficiency factor in the softened strut and tie model for the ultimate shear strength prediction of steel RC deep beams based on experimental study. Issue 11 (28th July 2022) - Thomas, Job; Ramadass, S.
Abstract: In this paper, an empirical model for a strut efficiency factor ( β s ) is proposed and introduced in to the softened strut and tie model to predict the ultimate shear strength and the corresponding ultimate load of simply supported steel reinforced concrete (RC) deep beams under 4-point bending without transverse reinforcements. The proposed model accounts for the influence of shear span to depth ratio ( a / d ), concrete compressive strength ( f c ' ), area of steel reinforcement ( A s ), diagonal strut angle ( θ ) and width of loading plate ( l t ) . In addition, an empirical model for a stiffness degradation coefficient ( k f ) accounting for the influence of overall depth of the beam ( D ) and the diagonal strut angle ( θ ) is proposed and introduced in to a deflection prediction model to predict the corresponding ultimate deflection. In this study, 12 numbers of steel RC deep beams are cast and tested. The empirical models are proposed for the strength and the deflection prediction using regression analysis based on the test results of 373 and 86 steel RC deep beams respectively, which includes the 12 test beams of the present study. The proposed models are validated by accounting for the maximum range of the parameters involved in the database. The predictions based on the proposed models are compared with the predictions based on the other models. The comparison shows that the proposed models can accurately predict the ultimate load and the mid span deflection of the steel RC deep beams.